Plastic Deformation Nucleation in Elastically Loaded CuNi Alloy during Nanoindentation - Kryzhevich D. S. Dmitrii; Korchuganov A. V. Aleksandr; Zolnikov K. P. Konstantin; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen